Islamic Based Educational Games in the Social Development of Early Childhood at RA Darul Hasanah - Akhlak, Faza Karimatul (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
This study aims to analyze the contribution of Islamic-based educational games to the social development of early childhood at RA Daarul Hasanah. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving two teachers and twelve children aged 5–6 years from Group B. The findings reveal that Islamic educational games positively influence children’s social competence, including improved social interaction, empathy development, and the formation of Islamic social character. Children became more active in communication, cooperation, and demonstrated honesty, discipline, and responsibility during play activities. Teachers applied a reflective learning approach to help children understand the moral values embedded in each play experience. Theoretically, this study supports Vygotsky’s theory of the importance of social interaction in child development and aligns with Al-Attas’s (1991) concept of insan adabi, which emphasizes character formation through the integration of knowledge, values, and action. Thus, Islamic-based educational games play a crucial role in fostering holistic social and moral development in early childhood.